Structure–function relationships between residence time distribution and lignocellulosic deconstruction and fermentation yield of wheat straw during reactive extrusion pretreatment - Huimin Zhang; Jiantao Guo; Xiaodong Xu; Suan Shi; Xian Liu; Lujia Han (Bioresource Technology, 2027)

Responses of biogeochemical cycles to polyethylene microplastics exposure during aerobic fermentation of dairy manure - Qianting Zhuo; Ranran Wei; Ya Su; Haochen Shao; Lujia Han; Guangqun Huang (Bioresource Technology, 2026)

Influence of soil types with different soil-forming process on the qualitative and quantitative detection of microplastics by near-infrared spectroscopy - Linwei Cai; Zengling Yang; Zhuolin Shi; Xintong Zhang; Jinzhao Li; Lujia Han (Journal of Environmental Sciences, 2026)

Cellular-scale milling enhances xylo-oligosaccharides selectivity and polyphenols co-production in sugarcane bagasse hydrothermal conversion - Kaili Ding; Jun Xu; Liuyu Zong; Huarong Lu; Xueyan Liang; Lujia Han; Weihua Xiao (Food Chemistry, 2026)

Hydrothermal carbonization coupled with steam gasification upcycles biomass-PVC waste into CO2-suppressed syngas - Quan Liu; Guanyu Zhang; Xuesong Zhang; Lujia Han (Journal of Hazardous Materials, 2026)

One-pot synthesis of lignin-based carbon quantum dots via PTA-catalyzed HPAC oxidation: Mechanisms, structure, and applications in selective fluorescence detection of Cr6+ - Xueyan Liang; Kaili Ding; Hui Zhang; Yinghui He; Lujia Han; Xuesong Zhang; Weihua Xiao (Journal of Environmental Chemical Engineering, 2026)

Influence of soil types defined by soil genesis on the qualitative and quantitative detection of microplastics in soil by mid-infrared spectroscopy - Linwei Cai; Chunxu Wan; Zengling Yang; Zhuolin Shi; Xintong Zhang; Jinzhao Li; Lujia Han (Journal of Environmental Chemical Engineering, 2026)

Cultivar-specific divergence in volatile aroma profiles of heat-stressed grapes uncovered via GC×GC-TOFMS - Chenlu Du; Xinrui Liu; Minying Liu; Mingzheng Han; Zhen Zhang; Yuanyuan Xu; Yue Song; Yuanxu Teng; Dongying Fan; Junpeng Li; Lujia Wang; Juan He; et al. (Food Chemistry, 2026)

Toward industrial biorefineries: Process simulation and economic feasibility of high-solid enzymatic hydrolysis using alkali-assisted ball-milled corn stover - Hui Zhang; Yufeng Tan; Kaili Ding; Yinghui He; Yangyang Li; Lujia Han; Weihua Xiao (Bioresource Technology Reports, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Co-gasification coupled with steam reforming of inseparable livestock biowastes for green hydrogen-rich syngas production - Jiarui Zhu; Qiuhan Pu; Liang Wang; Ge Kong; Zengjian Guo; Ru Sun; Guanyu Zhang; Xin Zhang; Xuesong Zhang; Lujia Han (Journal of Environmental Chemical Engineering, 2026)

Scalable upcycling of medical plastic waste using metals-doped hierarchically porous biocarbon for tunable fuel-grade hydrocarbons or H2-enriched fuel gas - Guanyu Zhang; Qing Cheng; Ge Kong; Yuan Jiang; Xin Zhang; Tianqi Cao; Jingyou Bi; Jin Wang; Fangqi Liu; Chun Shan; Xuesong Zhang; Lujia Han (Fuel, 2026)

Unlocking high-solid biorefining of corn stover via ball milling: paving the way for profitability - Kaili Ding; Xueyan Liang; Xiwen Jia; Aihua Deng; Haitao Yu; Lujia Han; Jiajie Xu; Weihua Xiao (Chemical Engineering Journal, 2026)

Physically mixed CaO-Ni dual-functional materials for integrated CO2 capture and conversion via CH4 dry reforming: Critical role of the proximity - Xizhe Zhang; Yilin Liao; Bingcan Yang; Wen Liu; Weixin Xu; Sicong Tian; Lujia Han (Chemical Engineering Journal, 2026)

The pattern of greenhouse gas emissions by membrane-covered aerobic composting of vegetable waste: From microbial community composition and function standpoint - Li Luo; Yuli Shen; Huiqi Sun; Lujia Han; Suan Shi (Journal of Environmental Chemical Engineering, 2026)

A highly efficient and recyclable bone char for catalytic pyrolysis of polypropylene - Jiale Liu; Yuyu Li; Xuesong Zhang; Zengling Yang; Xian Liu; Lujia Han (Journal of Environmental Management, 2026)

The targeted removal of aromatic inhibitors in dilute acid prehydrolysate of corn stover by KOH-modified biochar for the efficient production of lactic acid - Yuli Shen; Li Luo; Karfee Chong; Yi Yang; David Blersch; Vekes Balasundram; Suan Shi; Lujia Han (Journal of Environmental Management, 2025)

Dry alkali-ball milling for high-solid conversion of biomass to sugar and ethanol: Comparison with conventional ball milling - Kaili Ding; Hao Lin; Xueli Chen; Xiwen Jia; Suan Shi; Xiaojun Guo; Ling Zhou; Lujia Han; Weihua Xiao (Fuel, 2025)

In-situ visual delignification and cell-scale kinetics modeling using confocal Raman microscopy - Yuanping Huang; Zengling Yang; Chenjun Ge; Zhuolin Shi; Xinlei Wang; Lujia Han (Bioresource Technology, 2025)

In situ aging mechanism of polyethylene microplastics during aerobic fermentation: Driven by fermentation conditions and plastic-degrading microorganisms - Qianting Zhuo; Wentao Gao; Zhuoyi Zhang; Ya Su; Ranran Wei; Lujia Han; Guangqun Huang (Chemical Engineering Journal, 2025)

In situ generation of peracetic acid using phosphotungstic acid: A one-pot strategy for selective delignification of corn stover - Xueyan Liang; Zhen Hao; Xiwen Jia; Kaili Ding; Hui Zhang; Aihua Deng; Haitao Yu; Lujia Han; Weihua Xiao (Bioresource Technology, 2025)

Degradation-catalysis of polypropylene into liquid fuel-range iso-olefins using Zn and Ni-incorporated microporous carbon - Qing Cheng; Guanyu Zhang; Wei Li; Yuan Jiang; Ge Kong; Xin Zhang; Jin Wang; Fangqi Liu; Chun Shan; Xuesong Zhang; Lujia Han (Journal of Hazardous Materials, 2025)

From black to green - A critical review of thermochemical valorization of black liquor - Quan Liu; Xuesong Zhang; Lujia Han (Chemical Engineering Journal, 2025)

Coupled effects of amoxicillin and copper on high-risk antibiotic resistance gene dynamics during dairy manure aerobic composting - Ya Su; Ranran Wei; Qianting Zhuo; Chen Fang; Pingfan Wu; Lujia Han; Guangqun Huang (Chemical Engineering Journal, 2025)

Preparation of capsicum leaf protein/lignocellulose nanocrystals/corn starch composite antibacterial packaging films by in-situ green-synthesized silver oxide nanoparticle - Qingyu Qin; Xinyan Zhang; Wenying Liu; Lin Lin; Xian Liu; Lujia Han (Food Chemistry, 2025)

Valorizing copper-contaminated manure into biochar for tetracycline adsorption: Dynamics and interactions of tetracycline adsorption and copper leaching - Haoxiang Xiong; Xiaojing Zhao; Kai Song; Di Gao; Zengling Yang; Lujia Han (Waste Management, 2025)

Enhancement of caproate production via carboxylate chain elongation with sequential fermentation facilitated by biochar: A corn stover full-component utilization perspective - Xiwen Jia; Dong Liu; Jiajie Xu; Hui Zhang; Luoyang Liu; Lujia Han; Weihua Xiao; Suan Shi (Bioresource Technology, 2025)

Solvent-free upcycling of agricultural plastic waste using in situ self-assembly metal nanoparticles co-doped microporous carbocatalyst for advanced transportation fuels - Ge Kong; Xiangru Yuan; Xiaojing Zhao; Jin Wang; Weizheng Zhong; Rongbin Qiu; Kai Song; Qing Cheng; Xuesong Zhang; Lujia Han (Journal of Hazardous Materials, 2025)

Study on a potential bone char catalyst for high efficiency catalytic pyrolysis of polypropylene plastic - Jiale Liu; Yuyu Li; Wenbei Deng; Yongyang Wu; Dongjiao Chen; Xuesong Zhang; Xian Liu; Lujia Han (Fuel, 2025)

Novel CRM cosine similarity mapping strategy for simultaneous in-situ visual profiling lignocellulose in plant cell walls - Yuanping Huang; Keke Liao; Zengling Yang; Sicong Tian; Xiangru Yuan; Xingming Sun; Zichao Li; Lujia Han (Carbohydrate Polymers, 2025)

Green hydrogen and porous carbon materials co-harvested through CO2-steam co-mediated gasification - Xin Zhang; Chuan Qin; Yi Lu; Quan Liu; Hongkang Liu; Chun Wang; Guanyu Zhang; Ge Kong; Kejie Wang; Jing Li; Jianying Shang; Xuesong Zhang; et al. (Bioresource Technology, 2025)

A comprehensive review of bone char: Fabrication procedures, physicochemical properties, and environmental application - Yuyu Li; Jiale Liu; Baoping Wei; Xuesong Zhang; Xian Liu; Lujia Han (Science of The Total Environment, 2024)

Strategies for enhancing short- and medium-chain fatty acids synthesis from corn stover-based sugar: A new perspective on co-culture - Xiwen Jia; Jiajie Xu; Luoyang Liu; Xueyan Liang; Yinghui He; Lujia Han; Weihua Xiao (Journal of Environmental Chemical Engineering, 2024)

A systematical comparation of Cu (II) adsorption behavior and mechanism between biomass fly ash and biogas residue pyrolysis char - Xiaojing Zhao; Haoxiang Xiong; Kai Song; Laiyuan Yu; Xiaoxiao Zhang; Lujia Han (Bioresource Technology Reports, 2024)

A novel micro-CT approach for in situ visualization of the spatial dynamics of mesovoids in aerobic composting piles - Rongbin Qiu; Weizheng Zhong; Hehu Zhang; Ying Zhu; Zengling Yang; Lujia Han (Journal of Environmental Management, 2024)

Upcycling of medical protective clothing for H2 production through catalytic steam reforming over Ni-impregnated catalysts - Kejie Wang; Jiajia Yu; Fangqi Liu; Jin Wang; Ge Kong; Guanyu Zhang; Suan Shi; Xuesong Zhang; Lujia Han (Journal of Environmental Chemical Engineering, 2024)

Feasibility of biomass-based flexible and transparent AuNPs-acetylcellulose membrane for multifarious surface-enhanced Raman spectroscopy detection - Haitao Yu; Dongyi Guo; Xueli Chen; Xueyan Liang; Zengling Yang; Lujia Han; Weihua Xiao (Analytica Chimica Acta, 2024)

Energy-efficient production of sustainable industrial process heat with a parabolic dish-conical cavity solar collector - Chen Fan; Xizhe Zhang; Wen Liu; Shuangmei Han; Weixin Xu; Sicong Tian; Lujia Han (Journal of Cleaner Production, 2024)

Capsicum leaf protein-based bionanocomposite films for packaging application: Effect of corn starch content on film properties - Qingyu Qin; Wenying Liu; Bing Gao; Xinyan Zhang; Lujia Han; Swee Leong Sing; Xian Liu (Food Chemistry, 2024)

Upcycling heteroatoms-containing plastics via bimetallic synergistic catalysis: Unveiling the role of O and Cl in C-H bond cleavage - Yuan Jiang; Guanya Ji; Fangqi Liu; Ge Kong; Linling Zhou; Guanyu Zhang; Kejie Wang; Xuesong Zhang; Lujia Han (Chemical Engineering Journal, 2024)

Insights into PVC-promoted hydrothermal carbonization of manure: Dechlorination, inorganic metals removal, and combustion behaviors - Quan Liu; Guanya Ji; Xintong Li; Guanyu Zhang; Xin Zhang; Xuesong Zhang; Lujia Han (Chemical Engineering Journal, 2024)

Optimization of poly(3-hydroxybutyrate) production with simulating corn stover hydrolysates by Paraburkholderia sacchari - Xueyan Liang; Dong Liu; Kaili Ding; Xiwen Jia; Hui Zhang; Luoyang Liu; Yinghui He; Xian Liu; Lujia Han; Weihua Xiao (Biocatalysis and Agricultural Biotechnology, 2024)

Microscopic FT-IR imaging-based meat and bone meal species discrimination using the screened matrix fragments-related spectral pixels and tableting pretreatment - Bing Gao; Qingyu Qin; Jiale Liu; Lujia Han; Xian Liu (Computers and Electronics in Agriculture, 2024)

Microbial mechanisms involved in negative effects of amoxicillin and copper on humification during composting of dairy cattle manure - Ya Su; Ling Zhou; Qianting Zhuo; Chen Fang; Jia You; Lujia Han; Guangqun Huang (Bioresource Technology, 2024)

In-situ registration subtraction image segmentation algorithm for spatiotemporal visualization of copper adsorption onto corn stalk-derived pellet biochar by micro-computed tomography - Kai Song; Haoxiang Xiong; Xiaojing Zhao; Jieyu Wang; Zengling Yang; Lujia Han (Bioresource Technology, 2024)

Cow Manure Pellet Biochar: Leaching of Cu(II) and Its Corresponding Influences on Tetracycline Adsorption - Haoxiang Xiong; Xiaojing Zhao; Kai Song; Zengling Yang; Lujia Han (Water, Air, & Soil Pollution, 2024)

Wheat straw biochar as an additive in swine manure Composting: An in-depth analysis of mixed material particle characteristics and interface interactions - Xueqin He; Zhihao Peng; Yuxiong Zhu; Yufeng Chen; Yuanping Huang; Jingpeng Xiong; Chen Fang; Shurong Du; Long Wang; Ling Zhou; Guangqun Huang; Lujia Han (Waste Management, 2024)

Upcycling of hazardous plastic waste by CO2 transformation-enhanced steam reforming over MgO-promoted Ni/C bifunctional catalyst - Xuesong Zhang; Kejie Wang; Fangqi Liu; Ge Kong; Guanya Ji; Yuan Jiang; Guanyu Zhang; Quan Liu; Qing Cheng; Tianqi Cao; Hongkang Liu; Xin Zhang; et al. (Chemical Engineering Journal, 2024)

Machine learning-aided hydrothermal carbonization of biomass for coal-like hydrochar production: Parameters optimization and experimental verification - Quan Liu; Guanyu Zhang; Jiajia Yu; Ge Kong; Tianqi Cao; Guanya Ji; Xuesong Zhang; Lujia Han (Bioresource Technology, 2024)

Influence of pyrolysis atmosphere, temperature, and particle size co-regulation on the physicochemical properties of bone char - Yuyu Li; Jiale Liu; Lujia Han; Baoping Wei; Xian Liu (Journal of Environmental Chemical Engineering, 2023)

Inhibitory effects and action mechanism of five antioxidant peptides derived from wheat gluten on cells oxidative stress injury - Wenying Liu; Jie Ren; Hanshuo Wu; Xinxue Zhang; Lujia Han; Ruizeng Gu (Food Bioscience, 2023)

Multivariate and multiscale investigation of ammonia production and emission mechanisms during membrane-covered cattle manure/wheat straw aerobic composting - Jinpeng Xiong; Qianting Zhuo; Zhuolin Shi; Xueqin He; Lujia Han; Guangqun Huang (Chemical Engineering Journal, 2023)

Catalytic hydrothermal co-liquefaction of sewage sludge and agricultural biomass for promoting advanced biocrude production - Guanyu Zhang; Quan Liu; Xintong Li; Ge Kong; Tianqi Cao; Qing Cheng; Ziyi Zhang; Xuesong Zhang; Lujia Han (Journal of Cleaner Production, 2023)

Nitrogen evolution during membrane-covered aerobic composting: Interconversion between nitrogen forms and migration pathways - Jinpeng Xiong; Qianting Zhuo; Ya Su; Huiwen Qu; Xueqin He; Lujia Han; Guangqun Huang (Journal of Environmental Management, 2023)

Insight into effect of pigment removal on leaf protein-based bionanocomposite film properties - Qingyu Qin; Jiale Liu; Xinyan Zhang; Wenying Liu; Lujia Han; Swee Leong Sing; Xian Liu (Food Hydrocolloids, 2023)

Improving hydrogen-rich gas production from biomass catalytic steam gasification over metal-doping porous biochar - Ge Kong; Quan Liu; Guanya Ji; Haoyang Jia; Tianqi Cao; Xuesong Zhang; Lujia Han (Bioresource Technology, 2023)

Kinetics and modeling of Pb (II) adsorption in pellet biochar based on micro-computed tomography characterization - Hehu Zhang; Weizheng Zhong; Rongbin Qiu; Lujia Han (Bioresource Technology, 2023)

CO2-mediated catalytic upcycling of plastic waste for H2-rich syngas and carbon nanomaterials - Xuesong Zhang; Yuan Jiang; Ge Kong; Quan Liu; Guanyu Zhang; Kejie Wang; Tianqi Cao; Qing Cheng; Ziyi Zhang; Guanya Ji; Lujia Han (Journal of Hazardous Materials, 2023)

Combined effects of amoxicillin and copper on nitrogen transformation and the microbial mechanisms during aerobic composting of cow manure - Ya Su; Jinpeng Xiong; Chen Fang; Huiwen Qu; Lujia Han; Xueqin He; Guangqun Huang (Journal of Hazardous Materials, 2023)

Safety production and application of dairy bedding by membrane-covered aerobic fermentation: Insight into the evolution of mastitis pathogens and harmful gas emissions - Hongjie Yin; Chen Fang; Xueqin He; Hao Yu; Yuying Liang; Lujia Han; Guangqun Huang (Journal of Environmental Chemical Engineering, 2023)

Gasification integrated with steam co-reforming of agricultural waste biomass over its derived CO2/O2/steam-mediated porous biochar for boosting H2-rich syngas production - Xuesong Zhang; Ge Kong; Xin Zhang; Kejie Wang; Quan Liu; Suan Shi; Lujia Han (Journal of Environmental Chemical Engineering, 2023)

Effects of micro-positive pressure environment on nitrogen conservation and humification enhancement during functional membrane-covered aerobic composting - Jinpeng Xiong; Ya Su; Huiwen Qu; Lujia Han; Xueqin He; Jianbin Guo; Guangqun Huang (Science of The Total Environment, 2023)

Effects of functional membrane coverings on carbon and nitrogen evolution during aerobic composting: Insight into the succession of bacterial and fungal communities - Jinpeng Xiong; Ya Su; Xueqin He; Lujia Han; Guangqun Huang (Bioresource Technology, 2023)

A Micro-CT Approach for 3D In-Situ Visualizing the Cu (II) Adsorption in Corn Cob Biochar - Haoxiang Xiong; Lujia Han; Hehu Zhang; Kai Song; Zengling Yang (Water, Air, & Soil Pollution, 2023)

Determining the Effect of pH on the Partitioning of Neutral, Cationic and Anionic Chemicals to Artificial Sebum: New Physicochemical Insight and QSPR Model - Senpei Yang; Lingyi Li; Tao Chen; Lujia Han; Guoping Lian (Pharmaceutical Research, 2018)

In Silico Prediction of Percutaneous Absorption and Disposition Kinetics of Chemicals - Longjian Chen; Lujia Han; Ouarda Saib; Guoping Lian (Pharmaceutical Research, 2015)

Kinetics and Equilibrium of Solute Diffusion into Human Hair - Liming Wang; Longjian Chen; Lujia Han; Guoping Lian (Annals of Biomedical Engineering, 2012)